Childhood socio-economic disadvantage in Austria A snapshot of key challenges - Clarke, Chris (OECD Papers on Well-being and Inequalities, 2023)
In Europe, the introduction of the Council Recommendation establishing a European Child Guarantee has helped put concerns relating to childhood disadvantages higher up on the policy agenda. Structured around ensuring effective access to a series of key child services, the ultimate goal of the European Child Guarantee is to promote opportunities for children from disadvantaged backgrounds and help stop the transmission of poverty and social exclusion across generations. But as European countries move forward with their plans for implementation, it is important to understand what child disadvantage looks like, as well as the potential lifelong effects it can have on children's lives. This paper explores childhood socio-economic disadvantage in Austria from a comparative perspective. It sketches the breadth and depth of child poverty and material deprivation in Austria today, and discusses the potential longer-run economic costs of childhood disadvantage once disadvantaged children reach adulthood, based on findings from Clarke et al. (2022). It also discusses key policy challenges Austria will need to consider to tackle childhood socio-economic disadvantage